Conservation of resources and suicide proneness after oilrig disaster. Issue 1 (2nd January 2020) - Bell, Tyler Reed; Langhinrichsen-Rohling, Jennifer; Selwyn, Candice N.
Abstract: The current study applied the Conservation of Resources (COR) disaster theory to explain suicide proneness after the Deepwater Horizon oilrig explosion. We had 213 residents in affected areas with complete measures of resource stability, distress, and coping 18 months after the disaster. Overall, 10% expressed clinically elevated suicide proneness. The COR model had excellent fit that accounted for 41% of inter-individual differences in suicide proneness. Aligned with theory, residents lacking resources who experienced distress and coped by avoidance were more suicide-prone. Fostering resource stability and constructive coping after catastrophe may help reduce suicide proneness and prevent suicide in disaster-impacted citizens.